Bacoside A Induces Tumor Cell Death in Human Glioblastoma Cell Lines through Catastrophic Macropinocytosis - John, Sebastian; Sivakumar, K. C.; Mishra, Rashmi (Frontiers in Molecular Neuroscience, 2017)
Glioblastoma multiforme (GBM) is a highly aggressive type of brain tumor with an extremely poor prognosis. Recent evidences have shown that the 'biomechanical imbalances' induced in GBM patient-derived glioblastoma cells and in vivo via the administration of synthetic small molecules, may effectively inhibit disease progression and prolong survival of GBM animal models. This novel concept associated with de novo anti-GBM drug development has however suffered obstacles in adequate clinical utility due to the appearance of unrelated toxicity in the prolonged therapeutic windows. Here, we took a 'drug repurposing approach' to trigger similar physico-chemical disturbances in the GBM tumor cells, wherein, the candidate therapeutic agent has been previously well established for its neuro-protective roles, safety, efficacy, prolonged tolerance and excellent brain bioavailability in human subjects and mouse models. In this study, we show that the extracts of an Indian traditional medicinal plant Bacopa monnieri and its bioactive component Bacoside A can generate dosage associated tumor specific disturbances in the hydrostatic pressure balance of the cell via a mechanism involving excessive phosphorylation of CaMK2A enzyme that is further involved in the release of calcium from the smooth endoplasmic reticular networks. High intracellular calcium stimulated massive macropinocytotic extracellular fluid intake causing cell hypertrophy in the initial stages, excessive macropinosome enlargement and fluid accumulation associated organellar congestion, cell swelling, cell rounding and membrane rupture of glioblastoma cells; with all these events culminating into a non-apoptotic, physical non-homeostasis associated glioblastoma tumor cell death. These results identify glioblastoma tumor cells to be a specific target of the tested herbal medicine and therefore can be exploited as a safe anti-GBM therapeutic.